ANALISIS KEBUTUHAN PENGOPERASIAN ANGKUTAN ANTAR JEMPUT (CAR POOLING) BAGI SISWA SEKOLAH DI KOTA DENPASAR - Dewa Ayu Nyoman Sriastuti; A.A. Rai Asmani K.; Nyoman Surayasa (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2018)
ABSTRACT The activities of taking and picking up by parents of students often cause traffic congestion around the school. This happens almost every day, especially in the morning, when school starts and in the afternoon, when school hours are over. There is not an adequate parking space available at the school, so the introductory and pick-up people use the body of the road to park when delivering and picking up. To overcome this, transportation facilities are needed which can reduce the number of vehicles used to deliver and pick up school students. The information that you want to know from the survey on respondents is monthly family income, factors that are considered important in choosing the type of transport, the vehicle used by students, whether students go to school or alone, vehicle facilities for parents, travel time from home to school, desired service and departure schedule. The number of samples that have been set is a minimum number of samples from statistical calculations as respondents, where as respondents are parents of students. For this reason, questionnaires were distributed to the students, so that they were delivered to their parents. Based on the results of the questionnaire, the transport operation parameter data is obtained between the next pick-up, to get the number of passengers, service pattern, number of vehicles needed and the scheduled departure of transportation. The results of the analysis show that 74% of respondents want the first service pattern to be picked up on the main road at their respective address or residence. The estimated number of passengers to be served by the school student shuttle transportation in Denpasar City is 5148 people, with 214 vehicles needed. Vehicle departure schedule must be every 0.56 minutes starting at 06.50 WITA. Keywords: car pooling, operational, transportation